PENGARUH DEWAN KOMISARIS INDEPENDEN DAN KEPEMILIKAN MANAJERIAL TERHADAP KUALITAS LABA - Farida, Dessy Noor; Kusumumaningtyas, Metta (Sekolah Tinggi Ilmu Ekonomi Semarang, 2017)
Abstrak The Quality of earning is element that is often used by investors to take investment decisions. But the financial scandals that occurred, causing investors have crisis confidence in capital markets. Therefore, the necessary existence of a good corporate governance is very importance to create a financial statement that reflects the real condition of the company. The purpose of this study is to analyze the influence of independence board of commisioners on earnings quality which are moderated by the concentration of family ownership.                This study aims to analyze the role of independent board and managerial ownership on the quality of earnings is moderated by concentrated ownership. Earnings quality is proxied by discretionary accrual and concentrated ownership is calculated with F-PEC Score. Meanwhile, to measure independent commissioners use the proportion of commissioners who have no relationship with the company and for the managerial ownership is measured by the number of ownership shares held by the management of the total number of outstanding shares. Manufacturing firms listed in Indonesian Stock Exchange is the object of this study. Based on purposive sampling technique, it gets 96 firms. Multiple regression analysis using SPSS program. The result of the hypothesis test indicates that manajerial ownership and corporate size have significantly effect on discretionary accruals. This study also found a concentration of family ownership has insignificantly moderates the effect on an independent board to discretionary accruals.   Keywords: Earning management, good corporate governance, family ownership